2006
DOI: 10.1306/10120505003
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and seismic interpretation of the Perdido fold belt: Northwestern deep-water Gulf of Mexico

Abstract: We interpret the Perdido fold belt to be composed of detachment folds flanked by megascopic-scale kink bands. The two previous principal fold models for the Perdido fold belt incorporated components of large-scale faulting: an imbricate fault-bend fold model and a high-angle, reverse-faulted detachment fold model. We interpret the Perdido fold belt to be fold dominated. The belt consists of detachment folds overlying a ductile decollement layer. The detachment fold crests are bounded by kink bands, which are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…It should be noted that the seismic cross section shown in Figure 3b does not run perpendicular to the fold axis in the distal part and therefore displays larger apparent wavelengths. Furthermore, eight individual folds have been identified in the recent work of Camerlo and Benson [2006] (Figure 3a), whereas previous studies identified less folds [Trudgill et al, 1999;Fiduk et al, 1999;Rowan et al, 2000] (inset of Figure 1 and Figure 3b).…”
Section: Description Of the Perdido Fold Beltmentioning
confidence: 88%
See 1 more Smart Citation
“…It should be noted that the seismic cross section shown in Figure 3b does not run perpendicular to the fold axis in the distal part and therefore displays larger apparent wavelengths. Furthermore, eight individual folds have been identified in the recent work of Camerlo and Benson [2006] (Figure 3a), whereas previous studies identified less folds [Trudgill et al, 1999;Fiduk et al, 1999;Rowan et al, 2000] (inset of Figure 1 and Figure 3b).…”
Section: Description Of the Perdido Fold Beltmentioning
confidence: 88%
“…The detailed nature of these narrow zones of deformation in between individual folds cannot be determined with the current model resolution. They might represent kink bands, shear bands or a continuum mechanics approximation of thrust faults, but will here be referred to as kink bands because they resemble the nature of the narrow deformation zones of the PFB [Camerlo and Benson, 2006] (Figures 10b and 10c, section 5.3). Ongoing shortening is ultimately absorbed in a single thrust fault at the pinch-out of the salt (Figure 9c).…”
Section: Evolution Of the Reference Modelmentioning
confidence: 99%
“…Gravity driven compression at the lower Rio Grande slope deformed a thick roof sediment above the salt there. The salt could not pierce the thick roof, and instead facilitated formation of kink-bands and pop-up structures Camerlo and Benson, 2006). The similar Perdido Type in the study area thus may also hint to a compression event occurred at the Miocene time.…”
Section: The Trigger Of the Structural Initiationmentioning
confidence: 72%
“…Seismic images of fold and thrust belts are poor in general because of steeply dipping beds, velocity inversions, and their complex internal structure (e.g., Shaw et al, 1999;Camerlo and Benson, 2006;Kostenko et al, 2008). This problem is compounded by passive roof duplexes and triangle zones (Shaw et al, 2005).…”
Section: Discussionmentioning
confidence: 99%